2012
DOI: 10.1109/tsp.2011.2178598
|View full text |Cite
|
Sign up to set email alerts
|

Joint Source and Relay Precoding Designs for MIMO Two-Way Relaying Based on MSE Criterion

Abstract: Properly designed precoders can significantly improve the spectral efficiency of multiple-input multipleoutput (MIMO) relay systems. In this paper, we investigate joint source and relay precoding design based on the mean-square-error (MSE) criterion in MIMO two-way relay systems, where two multi-antenna source nodes exchange information via a multi-antenna amplify-and-forward relay node. This problem is non-convex and its optimal solution remains unsolved. Aiming to find an efficient way to solve the problem, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
130
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 36 publications
0
130
0
Order By: Relevance
“…In this subsection, we illustrate how to achieve the DoF tuple d = (5, 3, 3, 1) under the antenna 6,5,4,4,9). In this example, there are min{5, 3} = 3…”
Section: Dof-region Achievabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this subsection, we illustrate how to achieve the DoF tuple d = (5, 3, 3, 1) under the antenna 6,5,4,4,9). In this example, there are min{5, 3} = 3…”
Section: Dof-region Achievabilitymentioning
confidence: 99%
“…Nowadays, a relay has become very much like a wireless gateway where multiple users share a common relay and communicate with each other. A typical representative is the two-way relay channel (TWRC) [4]- [6], where two users exchange information with each other through a relay. The success of two-way relaying owes to the invention of physical layer network coding (PLNC) [7], [8], which almost doubles the spectral efficiency compared with traditional one-way relaying [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the actual communication system, the reliability of the communication link could be ensured by minimizing the mean square error (MSE) of the receiver. In references [6,7] analysis under the condition of perfect channel state information (CSI), the precoding algorithm regards the MSE at two source nodes as the optimization target; the study [8] presents the complete CSI and the joint optimization method based on the criterion of MSE duality of two-way MIMO relay system. In [9], the precoding algorithm of amplifyand-forward MIMO two-way relay system based on channel capacity analysis is studied under limited channel feedback condition.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research work can be found in this area [1][2][3][4][5][6][7][8][9][10]. In [2][3][4][5][6], the multiple-input multiple-output (MIMO) techniques was deployed to increase the transmission rate. Various algorithms to optimize the resources and route planning can be found in [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%